2007
DOI: 10.1111/j.1444-2906.2007.01394.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cottonseed and soybean meal as partial replacement for fishmeal in diets for juvenile Japanese flounder Paralichthys olivaceus

Abstract: This study was conducted to investigate the effect of dietary supplementation of cottonseed and soybean meal (CS) on growth performance, feed utilization, and gossypol accumulation in juvenile (mean body weight 11 g) Japanese flounder Paralichthys olivaceus. Five isonitrogenous and isocaloric experimental diets (designated CS0, CS10, CS20, CS30, and CS40) containing 0, 10, 20, 30, and 40% CS mixture (1:1 w/w) were formulated. After 9 weeks of feeding trial, fish fed all diets did not show significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 60 publications
8
34
2
2
Order By: Relevance
“…No differences were observed when the level of free gossypol was 20 mg kg -1 or less (305 g cottonseed meal kg -1 diet). In juvenile Japanese flounder (Paralichthys olivaceus) Pham et al (2007) report no differences in growth or feed utilization fed diets containing a mix of cottonseed meal and soybean meal (1:1 ratio) up to 400 g kg -1 diet (total gossypol 320 mg kg -1 ). However, haemoglobin was reduced with increasing levels and at the highest level hematocrit was also reduced.…”
Section: Biological Effects In Fishmentioning
confidence: 99%
“…No differences were observed when the level of free gossypol was 20 mg kg -1 or less (305 g cottonseed meal kg -1 diet). In juvenile Japanese flounder (Paralichthys olivaceus) Pham et al (2007) report no differences in growth or feed utilization fed diets containing a mix of cottonseed meal and soybean meal (1:1 ratio) up to 400 g kg -1 diet (total gossypol 320 mg kg -1 ). However, haemoglobin was reduced with increasing levels and at the highest level hematocrit was also reduced.…”
Section: Biological Effects In Fishmentioning
confidence: 99%
“…They also suggested that dietary supplementation of iron and phosphorus could increase the inclusion of CSM for fishmeal replacement in diets for marine fish species. In the same species Pham et al (2007) shows that mixture of CSM and SBM with lysine and methionine supplementation can replace up to 30% fishmeal protein in diet for olive flounder at the early juvenile stage. However, they suggested that 20% fishmeal protein replacement by CSM (10%) and soybean meal (10%) can be optimum level as per the growth performance is considered.…”
Section: Growthmentioning
confidence: 99%
“…Toko et al (2008) observed the whole body content of calcium (Ca), phosphorus (P), potassium (K), zinc (Zn) and manganese (Mn) were markedly affected by dietary SBM level at high inclusions while increasing dietary CSM did not affect the content of these elements in carcass. Pham et al (2007) recommended that replacement of fishmeal protein up to 40% level by cottonseed meal and soybean meal by equal proportion with L-methionine and L-lysine supplementation did not affect the whole body compositions of Japanese flounder, Paralichthys olivaceus.…”
Section: Carcass Compositionmentioning
confidence: 99%
“…(Kim et al, 2002), / ) (Alam et al, 2002; , (Kim et al, 2006c;Kim et al, 2011a;Kim et al, 2012;) Pham et al, 2007;Ye et al, 2011). Cho et al, 2005;Lee et al, 2005; et al, 2006a, 2006bKim et al, 2008;An et al, 2011).…”
Section: 서 론mentioning
confidence: 99%